A New Species Pedibothr1um stegostomae N.Sp. (Eucestoda: Onchobothriidae) from Stegostoma tigrinum at Ratnagiri, M.S. India - Khamkar, D.D. (Recent Research in Science and Technology, 2011)
The present form deals with description of new species of the genus Pedibothrium stegostomae n.sp. differs from P. longispine Linton, 1909; P. brevispine Linton, 1909; P. hutsoni Southwell, 1924; P. lintoni Shinde et.al, 1980; P. vervalensis Shinde et.al. 1980, in the size of worm, shape of scolex, presence or absence of hooks, shape of hooks, number of segments, number of testes, shape of ovary, shape and position of vitellaria. As in P. lintoni and P. varvalensis 4 accessory suckers present but absent in remaining known species.